Impact of Gastrointestinal Symptoms in COVID-19: a Molecular Approach - Sonkar, Charu (SN Compr Clin Med, 2020)
The pandemic of novel coronavirus disease (COVID-19) caused by the Severe Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) creates an immense menace to public health worldwide. Currently, the World Health Organization (WHO) has recognized the novel coronavirus as the main cause of global pandemic. Patients infected with this virus generally show fever, nausea, and respiratory illness, while some patients also manifest gastrointestinal symptoms such as abdominal pain, vomiting, and diarrhea. Traces of SARS-CoV-2 RNA have been found in gastrointestinal cells. Further angiotensin converting enzyme 2 (ACE2) the known receptor for the virus is extensively expressed in these cells. This implies that gastrointestinal tract can be infected and can also present them as a replication site for SARS-CoV-2, but since this infection may lead to multiple organ failure, therefore identification of another receptor is a plausible choice. This review aims to provide comprehensive information about probable receptors such as sialic acid and CD147 which may facilitate the virus entry. Several potential targets are mentioned which can be used as a therapeutic approach for COVID-19 and associated GI disorders. The gut microbiomes are responsible for high levels of interferon-gamma which causes hyper-inflammation and exacerbates the severity of the disease. Briefly, this article highlights the gut microbiome’s relation and provides potential diagnostic approaches like RDT and LC-MS for sensitive and specific identification of viral proteins. Altogether, this article reviews epidemiology, probable receptors and put forward the tentative ideas of the therapeutic targets and diagnostic methods for COVID-19 with gastrointestinal aspect of disease.